The 1891 submarine eruption offshore Pantelleria Island (Sicily Channel, Italy): Identification of the vent and characterization of products and eruptive style. (24th June 2014) - Conte, A. M.; Martorelli, E.; Calarco, M.; Sposato, A.; Perinelli, C.; Coltelli, M.; Chiocci, F. L.
Abstract High‐resolution bathymetry and seafloor sampling have been used to characterize the 1891 submarine eruption of the Pantelleria volcanic complex. This submarine eruption has been documented mainly by historical reports, describing basaltic scoria bombs floating on the sea surface (i.e., lava balloons). In this study, the 1891 eruptive vent has been identified as a small cone (volume of ∼700, 000 m3) rising ∼90 m from 350 m w.d., and located within a newly discovered submarine volcanic field covering a wide area offshore from the NW coast of Pantelleria; recently, Kelly et al. (2012) confirmed this location by a multibeam and ROV survey. Pyroclasts from the 1891 eruption crop out directly on the seafloor and are fresh scoria clasts (i.e., small bombs, bomb fragments, and lapilli) and glass ash‐sized grains; both have been characterized in their morphology, textures, and geochemistry. The distinctive vesicularity and crystallization characteristics displayed by the scoriaceous pyroclasts reflect modes of degassing in both syn and posteruptive regimes; these characteristics, along with the distribution of deposits suggest for the strongest eruptive phase of the 1891 eruption a style analogous to Hawaiian fountaining. Glass grains from a buoyant plume were dispersed northward from the vent, up to distances of 1.5 km, redirected by the Levantine Intermediate Water. The identification of the 1891 submarine eruptive vent offshore Pantelleria, as well as the features of erupted pyroclasts improve our knowledge of submarine explosive eruptions that occur at shallow‐intermediate depths and, among these, of the rare eruptions producing lava balloons.